Integrated resource management for increased profitability in livestock farm - A success story (Indian Journal of Animal Production and Management, 2024)
An analysis was conducted to assess the impact of integrated resource management on overall profitability  of livestock farm at Livestock Farm Complex, NTR college of Veterinary Science, Gannavaram, Krishna  District Andhra Pradesh during the financial year 2018-19. Rain water harvesting and subsequent  utilization of harvested water for fish and fodder production led to a generation of an additional amount  of ` 26,40,180/- and ` 7,30,000/- from the sale of fodder slips and fish, respectively. The livestock and  poultry manure served as low cost input for fodder and fish production and green fodder decreased the  dependence on purchased feeds which in turn reduced the cost of feeding and improved the production,  reproduction and health status in farm livestock. Integrated resource management yielded an amount of  ` 70,04,033/- and ` 22,48,233/- lakhs gross and net income, respectively and the benefit to cost ratio  was 1.47 which was the highest in the history of entire university consisting several research stations and  farms at different places of the state.
Keywords: Integrated resource management; Livestock farm; Productivity; Profitability